(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
A cross-sectional population-based survey was conducted on a random sample of adolescents and young adults in the Fergana Valley of Uzbekistan. A total of 1,465 individuals (1,130 adolescents and 32 young men) were examined. The epidemiological program utilized standardized survey, biochemical, and instrumental methods to identify risk factors (RF) for arterial hypotension (AH). The population analysis demonstrated a relatively high prevalence of RF in adolescents and young men, as well as a correlation between AH and age and the 15 epidemiological risk factors in the study region. These results highlight the importance of conducting epidemiological studies of adolescents and young men to improve targeted AH prevention.